Clonal variation in growth, flowering and cone production in a seed orchard of Scots pine (Pinus sylvestris L.) in Turkey - Sıvacıoğlu, Ahmet; Ayan, Sezgin; Çelik, Durmuş Ali (African Journal of Biotechnology;Vol. 8 (17), 2009)
In this study, observations and measurements were made on five grafts for each of 30 clones in three successive years (2006, 2007 and 2008) on Scots pine (Pinus sylvestris) seed orchard established in 1995 by using 2 years-old grafts in Turkey. The examined characters were total height, diameter at base, number of branches, length of terminal shoot, length of lateral shoot, length of longest branch, number of male whorls, number of male flowers in a whorl, number of male flowers, length of male whorl, number of female flowers, cone number and crown diameter. Variation, broad-sense heritability and correlations between characters were estimated. Variation among clones was lower than among grafts for all studied characters. The broad sense heritability varied in a range of 0.15-0.38 for growth related characters, while it varied in a range of 0.15-0.59 for flowering related characters. The genetic variation for female and male flowering number is 36.5% and 82.8%, respectively. The number of flowers increased with the graft size. Significant correlations between the growth and flowering related characters varied in a range of 0.20-0.59 and 0.17-0.26 for male and female flowering, respectively.
Keywords: Scots pine, heritability, correlation, clone, graft, variation, cone, flowering, growth.